Students and Libraries: The Perspectives of Faculty in a Pakistani University - Muhammad Kashif; Ali Hassan; Hamayun Hassan (UiTM Publisher, 2011)
The purpose of this study is to explore student library use from the perspective of the faculty. An already developed instrument was used to collect data from full-time faculty members working in a private university located in the province of Punjab, Pakistan. The faculty strongly supported the idea of library based learning, student library use, assigning library-based tasks, and the crucial role of librarians in promoting a library culture. The respondents were not satisfied with the students' library use skills, availability of relevant and current data or the promotion of library use by the institution's top management. The current research is first of its kind in Pakistan and is based on data collected from a single university. Future research might be extended to other universities in the Pakistani or South Asian higher education sector. The study could be helpful to higher education policy to design customerdriven marketing strategies while marketing libraries to stakeholders.